439 Suffering at work among medical students: qualitative study using semi-structured interviews. (24th April 2018) - Le Provost, AS; Pougnet, R; Pietri, J; De Parscau, L; Loddé, B; Dewitte, JD
Abstract : Introduction: Suffering at work among health professionals is a hot topic. Medical students, doctors of tomorrow, are far from being spared. Prevalence of anxiety and mood disorders range from 20.3% to 69% for the former and from 12% to 30% for the latter. The purpose of this article was to determine these factors by qualitative research, according to medical students points of view. Methods: It was a qualitative study using semi-structured interviews. The analysis was done according to Grounded Theory . Results: 12 medical students were interviewed. They expressed difficulties at work and positive factors. Three major themes were identified in selective coding: occupational factors, 'study' factors and individual factors. All themes were both a source of well-being and ill-being according to the situations specified in the results. Conclusion: Studying medicine includes positive and negative aspects. Abandonment issues, lack of recognition and insufficient coaching emerge from our study. These results open lines of thought on the ways of improving formation of medical students.